Assessment of The Relation Between Red Cell Distribution Width and Atrial Fibrillation in Type-2 Diabetic Patiens - Demir, Aslıhan Dilara; Demir, Orhan (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
We aimed to investigate the level of red cell distribution width (RDW), in type-2 diabetic patients with atrial fibrillation. Patients aged 18 to 80 years old who were admitted to the internal medicine and cardiology outpatient clinics were enrolled. The data of the patient were retrospectively scanned from hospital database. 105 people were included in the study as 63 patients with diabetes mellitus and atrial fibrillation and 42 patients with diabetes mellitus and no atrial fibrillation. It was found that the age factor was statistically significant in men, women, and all patients between the groups, and Hb, hba1c, and LDL were statistically significant in men and all patients. The level of RDW is investigated in 2 groups of diabetic patients with and without atrial fibrillation. However, there was no significant difference between the two groups.